Adapentpronitrile, a New Dipeptidyl Peptidase-IV Inhibitor, Ameliorates Diabetic Neuronal Injury Through Inhibiting Mitochondria-Related Oxidative Stress and Apoptosis - Yang, Lu; Han, Wenli; Luo, Ying; Hu, Xiangnan; Xu, Ying; Li, Huan; Hu, Congli; Huang, Dan; Ma, Jie; Yang, Yang; Chen, Qi; Li, Yuke; et al. (Frontiers in Cellular Neuroscience, 2018)
Our previous studies indicated that adapentpronitrile, a new adamantane-based dipeptidyl peptidase-IV (DPP-IV) inhibitor, has a hypoglycemic effect and ameliorates rat pancreatic β cell dysfunction in type 2 diabetes mellitus through inhibiting DPP-IV activity. However, the effect of adapentpronitrile on the neurodegenerative diseases has not been studied. In the present study, we first found that adapentpronitrile significantly ameliorated neuronal injury and decreased amyloid precursor protein (APP) and amyloid beta (Aβ) expression in the hippocampus and cortex in the high fat diet/STZ rat model of diabetes. Furthermore, adapentpronitrile significantly attenuated oxidative stress, downregulated expression of the pro-apoptotic proteins BAX, cytochrome c, caspase-9, and caspase-3, and upregulated expression of the anti-apoptotic protein Bcl-2, although there was no effect on GLP-1R expression. At 30 min post-injection of adapentpronitrile (50 mg/kg) via the tail vein, its concentration in normal rat brain was 0.2034 ± 0.0094 μg/g. Subsequently, we further confirmed the neuroprotective effects and mechanism of adapentpronitrile in HT22 cells treated with high glucose (HG) and aluminum maltolate [Al(mal)3] overload, respectively. Our results showed significant decreases in mitochondrial membrane potential (MTP) and Bcl-2 expression, accompanied by a significant increase in apoptosis, reactive oxygen species (ROS) generation, and the expression of pro-apoptotic proteins in HT22 cells exposed to these stimuli. Adapentpronitrile treatment protected against neuronal injury, suppressed ROS generation, and reduced MTP and mitochondrial apoptosis in HT22 cells; however, DPP-IV activity was not detected. Our results suggest that adapentpronitrile protects against diabetic neuronal injury, at least partially, by inhibiting mitochondrial oxidative stress and the apoptotic pathway in a DPP-IV-independent manner.